A proposta biomecânica para a avaliação de sobrecarga na coluna lombar: efeito de diferentes variáveis demográficas na fadiga muscular - Barbosa, Fernando Sérgio Silva [UNESP]; Gonçalves, Mauro [UNESP] (Sociedade Brasileira de Ortopedia e Traumatologia, 2007)
OBJETIVOS: Analisar a fadiga de músculos lombares e determinar as variáveis demográficas relacionadas com a fadiga destes músculos. MÉTODOS: A atividade eletromiográfica (EMG) dos músculos iliocostal direito (IL-D), iliocostal esquerdo (IL-E), multífido direito (MU-D) e multífido esquerdo (MU-E) de 18 voluntários foi captada durante contrações isométricas sub-máximas. Valores de root mean square (RMS) e freqüência mediana (FM) foram correlacionados com o tempo de resistência isométrica (TRI). Slopes de RMS positivos e de FM negativos indicaram a ocorrência da fadiga muscular. Procedimentos de regressão múltipla foram realizados para verificar as variáveis demográficas relacionadas com a fadiga muscular. RESULTADOS: A fadiga foi identificada em todos os músculos e intensidades de contração (p<0.01), exceto no MU-E em 5% na análise do slope de RMS. Diferenças significantes foram encontradas entre o TRI de 5% e 15% (p=0.01), 5% e 20% (p=0.0002). Níveis de fadiga mais elevados estiveram bilateralmente presentes nos músculos multífidos na análise do slopes de FM. A associação do TRI, da idade e da massa corporal dos voluntários foi identificada como fator determinante para a ocorrência da fadiga nos músculos avaliados. CONCLUSÕES: Intervenções destinadas ao tratamento de problemas na coluna lombar devem considerar os vários fatores responsáveis pela fadiga dos músculos desta região.

OBJECTIVES: To assess low back muscles fatigue and to determine the demographic variables associated to fatigue on these muscles. METHODS: The electromyographic (EMG) activity of the right iliocostal (R-IL), left iliocostal (L-IL), right multifidus (R-MU) and left multifidus (L-MU) of 18 volunteers was recorded during submaximal isometric contractions. Root mean square (RMS) and median frequency (MF) values were correlated with isometric endurance time (IET). Positive RMS and negative MF slopes indicated occurrence of muscle fatigue. Multiple regression procedures were performed in order to verify the demographic variables related with the muscle fatigue. RESULTS: Fatigue was identified in all muscles and contraction intensities (p<0.01), except for MU-E at 5% in RMS slope analysis. Significant differences were found between the endurance time of 5% and 15% (p=0.01), 5% and 20% (p=0.0002). Higher levels of fatigue were found bilaterally in the multifidus muscles in the MF slope analysis. The combination of endurance time, age and body mass of the volunteers was identified as the determinant factor for the occurrence of muscle fatigue in the assessed muscles. CONCLUSIONS: Interventions designed to treat low back conditions must consider the several factors causing fatigue of muscles in this region.
A biomechamical approach for assessment of overload on lumbar spine: the effects of different demographic variables on muscle fatigue
Keywords: Biomecânica; Eletromiografia; Coluna vertebral; Fadiga muscular; Dor lombar; Protocolos clínicos; Biomechanics; Electromyography; Spine; Muscle fatigue; Low back pain; Clinical protocols